2018
DOI: 10.1016/j.aap.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-collision analysis of pedestrian and pedal-cycle accidents for the development of autonomous emergency braking systems

Abstract: The aim of this study was to describe the position of pedestrians and pedal cyclists relative to the striking vehicle in the 3 s before impact. This information is essential for the development of effective autonomous emergency braking systems and relevant test conditions for consumer ratings. The UK RAIDS-OTS study provided 175 pedestrian and 127 pedal-cycle cases based on in-depth, at-scene investigations of a representative sample of accidents in 2000-2010. Pedal cyclists were scattered laterally more widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Findings would need to be checked in car-to-VRU scenarios where VRU detection is more challenging compared to detection of a car which path is easier to predict and visibility generally higher. Accident reconstructions were used by Lenard et al (2018) to determine the requirement of ADAS sensors. From the analysis of pedestrian and cyclist accidents they found that the range needed to detect most of the pedestrians and cyclists is similar and in between 42 to 50m whereas the Field of View (FOV) varied significantly between cyclists and pedestrians: of ±80° for cyclists (total 160°) and only ±20° (total 40°) for pedestrians.…”
Section: Introductionmentioning
confidence: 99%
“…Findings would need to be checked in car-to-VRU scenarios where VRU detection is more challenging compared to detection of a car which path is easier to predict and visibility generally higher. Accident reconstructions were used by Lenard et al (2018) to determine the requirement of ADAS sensors. From the analysis of pedestrian and cyclist accidents they found that the range needed to detect most of the pedestrians and cyclists is similar and in between 42 to 50m whereas the Field of View (FOV) varied significantly between cyclists and pedestrians: of ±80° for cyclists (total 160°) and only ±20° (total 40°) for pedestrians.…”
Section: Introductionmentioning
confidence: 99%
“…1s). Lenard et al (2018) also analyzed parameters for an AEB applied to a British sample of 175 pedestrians and 127 cyclists' cases. Their study showed that with the same FOV definition as the one in this study, an AEB system with a FOV of 80° is enough to detect 90% of cyclists and 20° for pedestrians.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the antenna modules are evaluated for their coverage towards vulnerable road users in front of the car. In [37] the position of cyclists and pedestrians three seconds before impact are quantified. It is found that 90 % of pedestrians are located within ±20 • before impact, and that cyclists come from a wider range with 90 % within ±80 • .…”
Section: Discussionmentioning
confidence: 99%